Group-based Compassion-focused Therapy on Experiential Avoidance, Meaning-in-life, and Sense of Coherence in Female Survivors of Intimate Partner Violence with PTSD: A Randomized Controlled Trial - Daneshvar, Somayeh (Journal of interpersonal violence, 2022)
The current study was carried out to investigate the effects of compassion-focused therapy (CFT) on experiential avoidance, meaning-in-life, and sense of coherence (SoC) in women suffering from post-traumatic stress disorder (PTSD) due to the intimate partner violence (IPV).42 women suffering from PTSD due to the IPV exposure were randomized to the two groups of experimental and control (21 per group). All participants completed the questionnaires of experiential avoidance, meaning-in-life, and SoC as pre-test measures. The experimental group received eight sessions of CFT, while the controls did not receive any treatment. After that, all subjects responded to the questionnaires of experiential avoidance, meaning-in-life, and SoC as the post-test measures. Data were analyzed using one-way repeated measures MANOVA.Subjects of the experimental group indicated a greater reduction in post-test scores of experiential avoidance, and a significant rise in the level of meaning-in-life and its subscales including the presence of meaning-in-life and search for meaning-in-life when compared to the controls. Nevertheless, there was no change in the level of SoC as a function of CFT.Applying CFT can result in reducing experiential avoidance and raising the meaning of life in women with PTSD due to IPV exposure. CFT is highly recommended to strengthen the well-being of patients with PTSD and reduce the PTSD symptoms.